A study of the stability of contemporary rural Chinese Society - Ying, Xing (Springer Berlin Heidelberg, 2013)
This book is the last work of the author's trilogy on Chinese rural politics. In the background of prominent social conflicts since the 1990s during China's social transformation, the author conducted in-depth comparative analyses of several conflicts to understand the changes in goals, driving forces, and operating systems in the Chinese rural group contentions. His analyses also focused the changes in techniques and strategies of the governments' stability maintenance, as well as the complicated social and political consequences brought by these changes.   This book applies a very unique perspective - "vigor" in the Chinese culture - to understand contemporary rural contentious politics, in an attempt to overcome the problem brought by sense and sensibility and the confrontation between power and morality in the current contentious politics studies. And such a perspective successfully avoids the opposition between the transplanting school and rural school, which pushes forward the frontier of research on contentious political theories and rural societies.